The Impact of Psychological Capital on Faculty Motivation in Higher Education Institutions of Nepal: A Cross-Sectional Study - Ghimire, Binod; Karki, Dipendra; Dahal, Rewan Kumar; Joshi, Surendra Prasad (Journal of Business and Management, 2024)
Background: Faculty motivation is a critical determinant affecting academic performance and institutional achievement in higher education. Researchers have recognized psychological capital (PsyCap), which includes self-efficacy, hope, optimism, and resilience, as crucial factors influencing motivation. Nonetheless, its effect on faculty motivation remains inadequately examined in higher education settings in Nepal.Objectives: This study examines how PsyCap—hope, self-efficacy, resilience, and optimism—affects faculty motivation in higher education institutions. Its goal is to determine which PsyCap elements strongly influence faculty motivation.Methods: We administered a cross-sectional survey to 394 faculty members from diverse higher education institutions in Nepal. We used multiple regression analysis to analyze the effect of PsyCap components on faculty motivation.Results: The study revealed that hope, self-efficacy, and optimism had a substantial beneficial impact on faculty motivation, whereas resilience exhibited no significant effect. The research demonstrated that faculty motivation was significantly positively influenced by hope (β = 0.404, p < 0.001), optimism (β = 0.308, p < 0.001), and self-efficacy (β = 0.271, p < 0.001). Nevertheless, faculty motivation was not significantly influenced by resilience (β = 0.033, p = 0.224). These findings indicate that faculty members exhibiting elevated levels of self-efficacy, hope, and optimism demonstrate more motivation and engagement in their employment.Conclusion: The study substantiates that psychological capital, specifically hope, self-efficacy, and optimism, significantly contributes to faculty motivation. Institutions ought to invest in cultivating these psychological resources to enhance faculty job satisfaction, engagement, and performance.JEL Classification: I23, J24, M1